Pengaruh Latar Belakang Pendidikan Dan Kecerdasan Intelektual Terhadap Pemahaman Akuntansi Dengan Perilaku Belajar Sebagai Variabel Pemoderasi (Studi Empiris Pada Mahasiswa Program Studi S1 Akuntansi Universitas Muhammadiyah Metro) - Kurniawan, Edi; Hendri, Nedi; Sari, Gustin Padwa (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of educational background 1; and Intellectual Intelligence 2; Towards Understanding Accounting With Learning Behavior 3; As a moderating variable in students of the S1 Accounting Study Program, Muhammadiyah Metro University. The type of research used in this study is quantitative with a descriptive approach, in this study the researcher used primary data through questionnaires and the population in this study amounted to 484 students. The sampling technique in this research used purposive sampling by using several respondent criteria in order to obtain 118 respondents. The results of this study indicate that educational background has a positive and significant effect on accounting understanding, intellectual intelligence has a positive and significant effect on accounting understanding, The results of this study indicate that educational background and intellectual intelligence have a positive and significant effect on accounting understanding, learning behavior moderates educational background and intellectual intelligence on accounting understanding in undergraduate accounting students at Muhammadiyah Metro University.